2021
DOI: 10.29080/jpp.v12i1.531
|View full text |Cite
|
Sign up to set email alerts
|

Resiliensi di Masa Pandemi: Peran Efikasi Diri dan Persepsi Ancaman Covid-19

Abstract: Pandemi Covid-19 menuntut individu untuk dapat beradaptasi dengan kesulitan dan perubahan yang terjadi. Resiliensi sebagai salah satu fungsi adaptasi yang sehat merupakan bentuk kemampuan yang paling dibutuhkan untuk bertahan dalam kondisi pandemi ini. Penelitian ini bertujuan untuk mengeksplorasi bagaimana kemampuan resiliensi individu dipengaruhi oleh efikasi diri dan persepsi ancaman Covid-19. Partisipan dalam penelitian ini sebanyak 72 orang dengan rentang usia 15-32 tahun. Partisipan dipilih dengan menggu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
5
0
4
Order By: Relevance
“…Bao and Quyhn (2021) used a quantitative research approach with data collection techniques through questionnaires. Data were analyzed using multiple linear regression analysis (Sulastri & Jufri, 2021;Indrayanti et al, 2022;Bozovic et al, 2021). Meanwhile, Pitanatri & Putra's (2022) in their study has similarities with previous studies by Mananda et al (2021), namely using the Structural Equation Modeling (SEM) data analysis technique.…”
Section: Introductionmentioning
confidence: 77%
“…Bao and Quyhn (2021) used a quantitative research approach with data collection techniques through questionnaires. Data were analyzed using multiple linear regression analysis (Sulastri & Jufri, 2021;Indrayanti et al, 2022;Bozovic et al, 2021). Meanwhile, Pitanatri & Putra's (2022) in their study has similarities with previous studies by Mananda et al (2021), namely using the Structural Equation Modeling (SEM) data analysis technique.…”
Section: Introductionmentioning
confidence: 77%
“…In addition to staying adapting to new conditions or utilizing anything that can be done such as exercising at home, there are other research results that can be applied to increase resilience. According to research conducted by Sulastri and Jufri it was found that in this pandemic period individual resilience can be affected by selfefficacy and individual perceptions related to the threat of Covid-19 [19]. Confidence in solving problems or selfefficacy positively affects resilience [19].…”
Section: Distribution Of Resilience Of Each Aspectmentioning
confidence: 99%
“…According to research conducted by Sulastri and Jufri it was found that in this pandemic period individual resilience can be affected by selfefficacy and individual perceptions related to the threat of Covid-19 [19]. Confidence in solving problems or selfefficacy positively affects resilience [19]. The research is in line with Bandura's statement in [20] Self-efficacy is an individual's belief in his or her ability to perform tasks, solve problems, and overcome stressors in their life, greatly affects resilience.…”
Section: Distribution Of Resilience Of Each Aspectmentioning
confidence: 99%
“…Pandangan positif akan terlihat dari kemampuan anak dalam menyesuaikan diri dari suatu keadaan yang tidak menyenangkan dan penuh tekanan menjadi menyenangkan dan penuh pengharapan serta keadaan yang negatif diubah menjadi keadaan yang positif. Kemampuan ini biasanya dikenal dengan istilah resiliensi (Munawaroh & Mashudi, 2018;Sulastri & Jufri, 2021).…”
Section: Pendahuluanunclassified